Green tea increases anti-inflammatory tristetraprolin and decreases pro-inflammatory tumor necrosis factor mRNA levels in rats - Roussel Anne M; Coves Sara; Urban Joseph F; Dawson Harry D; Kari Frank; Kelly Meghan A; Cao Heping; Anderson Richard A (BMC, 2007)
Abstract Background Tristetraprolin (TTP/ZFP36) family proteins have anti-inflammatory activity by binding to and destabilizing pro-inflammatory mRNAs such as Tnf mRNA, and represent a potential therapeutic target for inflammation-related diseases. Tea has anti-inflammatory properties but the molecular mechanisms have not been completely elucidated. We hypothesized that TTP and/or its homologues might contribute to the beneficial effects of tea as an anti-inflammatory product. Methods Quantitative real-time PCR was used to investigate the effects of green tea (0, 1, and 2 g solid extract/kg diet) on the expression of Ttp family genes (Ttp/Tis11/Zfp36, Zfp36l1/Tis11b, Zfp36l2/Tis11d, Zfp36l3), pro-inflammatory genes (Tnf, Csf2/Gm-csf, Ptgs2/Cox2), and Elavl1/Hua/Hur and Vegf genes in liver and muscle of rats fed a high-fructose diet known to induce insulin resistance, oxidative stress, inflammation, and TNF-alpha levels. Results Ttp and Zfp36l1 mRNAs were the major forms in both liver and skeletal muscle. Ttp, Zfp36l1, and Zfp36l2 mRNA levels were more abundant in the liver than those in the muscle. Csf2/Gm-csf and Zfp36l3 mRNAs were undetectable in both tissues. Tea (1 g solid extract/kg diet) increased Ttp mRNA levels by 50-140% but Tnf mRNA levels decreased by 30% in both tissues, and Ptgs2/Cox2 mRNA levels decreased by 40% in the muscle. Tea (2 g solid extract/kg diet) increased Elavl1/Hua/Hur mRNA levels by 40% in the liver but did not affect any of the other mRNA levels in liver or muscle. Conclusion These results show that tea can modulate Ttp mRNA levels in animals and suggest that a post-transcriptional mechanism through TTP could partially account for tea's anti-inflammatory properties. The results also suggest that drinking adequate amounts of green tea may play a role in the prevention of inflammation-related diseases.